(untitled) (European Journal of Interdisciplinary Studies, 2016)
One of the legal intellectual property disciplines are copyrights which concerns artistic and literary works. Copyright is: bundle of exclusive legal rights that has to do with protection of literary and artistic works. It is granted to authors and artists to protect expressive works against unauthorized reproduction or distribution by third parties. Copyright protect “works”, expression of thoughts and ideas. Literary, dramatic, musical and artistic works must be original, it means not to be a copy. Copyright covers two other types of right: economic rights, the right of the owner to benefit financial reward from use of his work by others and moral rights which always have to do with original holder no matter if economic rights are transferred or not. Economic rights can be transferred. Bern Convention for the Protection of the Literary and Artistic Works is international key agreement and the oldest multilateral agreement in the field of copyright. Copyright subsists automatically on the creation of a work, no application needed, nor do any formalities apply. Nature of copyright is territorial and the minimum term of protection is life of the author plus 50 years after his/her death. In European Union and in certain number of countries, terms of protections of are extended to life of the author plus 70 years after his/her death.